2018
DOI: 10.1039/c8sm01597j
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of crystalline structures during gel spinning of ultra-high molecular weight polyethylene fibers

Abstract: The Weissenberg number during gel spinning controls the crystalline morphology of the as spun UHMWPE fiber. The final drawn crystalline morphology strongly depends on the starting as-spun crystalline structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For instance, high‐performance gel spun fibers are produced in the following steps: first, extrusion of gel fibers of diluted UHMWPE solution at high temperature followed by the formation of xerogel by removing solvent either by extraction or evaporation process and at last, drawing of extruded fiber in the hot environment below the melting temperature of the polymer, using a different set of rollers to achieve different draw ratio which ultimately enhances the performance of the fibers by inducing different structure and morphological changes. This axial tensile drawing process decreases the fiber diameter with an increasing draw ratio 13 . However, ultra‐stretching reinforcement could only be achieved when the drawing temperature of the polymer extrudate is more than the crystalline dispersion temperature 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, high‐performance gel spun fibers are produced in the following steps: first, extrusion of gel fibers of diluted UHMWPE solution at high temperature followed by the formation of xerogel by removing solvent either by extraction or evaporation process and at last, drawing of extruded fiber in the hot environment below the melting temperature of the polymer, using a different set of rollers to achieve different draw ratio which ultimately enhances the performance of the fibers by inducing different structure and morphological changes. This axial tensile drawing process decreases the fiber diameter with an increasing draw ratio 13 . However, ultra‐stretching reinforcement could only be achieved when the drawing temperature of the polymer extrudate is more than the crystalline dispersion temperature 14 …”
Section: Introductionmentioning
confidence: 99%
“…This axial tensile drawing process decreases the fiber diameter with an increasing draw ratio. 13 However, ultra-stretching reinforcement could only be achieved when the drawing temperature of the polymer extrudate is more than the crystalline dispersion temperature. 14 In order to contribute to this field, researchers are searching for different approaches for increasing the draw ratio to reach the theoretical tensile strength of 32 GPa and modulus values of 324 GPa of perfect polyethylene crystal by orienting and aligning all the molecular chains.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, many works have been done to achieve optimum bulk fiber properties via chemistry and processing (gel concentration, stretching speed, drawing temperatures (DT), and maximum draw ratio [DR], etc.) 3,15 . In previous investigations, the effects of extraction rates and spinning temperatures on the morphology and final mechanical properties of UHMWPE fibers were discussed by Hoogsteen et al 16 It was demonstrated that defects were existed in the fibrillar crystals of fibers prepared at lower spinning temperatures and higher extraction rates, resulting in lower mechanical performance of UHMWPE fibers.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, others claimed that fibers containing shish‐kebab structure were found to exhibit relatively poor drawability 23 . Recent works have characterized gel spinning parameters in quantitative terms by using Weissenberg number 15 . They found that there is a correlation between increased Wi and decreased crystallization time at Wi < 1.5, but the crystallization time is relatively constant for Wi > 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene is one of the most prominent commercial polymers, thanks to the various structures and grades available in terms of both density and branching, resulting in a third of the total plastic production worldwide . A relatively narrower market share of this total is occupied by ultrahigh molecular weight polyethylene (UHMWPE), the linear analogue with an average molecular weight exceeding 10 6 g/mol, used especially for high-end applications, such as in the biomedical sector. Because of the very long polymer chains being entangled in the melt state, this material shows very high values of melt viscosity, making it very difficult to process with conventional methods commonly used for thermoplastic materials. , Progress toward the direct synthesis of UHMWPE with a lower entanglement density (dis-UHMWPE) has been achieved via metallocene and post-metallocene catalysts. , Compared to commercial (entangled) UHMWPE, the dis-UHMWPE exhibits significantly enhanced processability . The disentangled character allows, for example, the solid-state processing of the polymer through molding and tensile stretching, resulting in uni-axially or bi-axially oriented samples that show very interesting thermal and mechanical properties. Variation in the molecular weight relates to the time required to reach the fully entangled equilibrium state, with longer chains requiring longer times to re-entangle .…”
Section: Introductionmentioning
confidence: 99%